BONSAI BERINGIN DAN SERUT SEBAGAI ALTERNATIF PENDAPATAN PETANI MILENIAL DI MASA PANDEMI COVID 19: BONSAI BERINGIN DAN SERUT ALTERNATIF PENDAPATAN PETANI MILENIAL - oryza sativa, rima dewi; Dita Serdani, Army (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2022)
Bonsai is a plant that is easy to care for and does not require extra care or attention. A little sun and a little water are needed to maintain a bonsai. It is from this wealth that the art of bonsai in Indonesia was born (Najoan et al, 2015). The art of maintaining and shaping this dwarf plant called "dwarf tree" actually began to be developed in China since the eleventh century, then entered Japan in the fifteenth century under a different name, "bonsai" (Nazaruddin, 2015). Bonsai also has health benefits, namely promoting a healthy lifestyle by purifying the air and the green charm of its leaves which is refreshing and pleasing to the eye to make it more peaceful and less stressful. In addition, in the era of the Covid 19 pandemic, the use of Air conditioners is not recommended for closed rooms because it is considered to transmit Covid 19. We are innovating and knowing the benefits of the Serut and Banyan bonsai ornamental plants, besides knowing the process of making the Serut and Banyan bonsai ornamental plants which were originally from plants. wild produce high oxygen levels